Monitoring and Assessment of the Microbial Populations and Chemical Characteristics of Paraquat Treated Soil - Dagze, John Kagana; Ishaku, B. Chimbekujwo; Dlama, Tari Tizhe (Cutting-edge Research in Agricultural Sciences Vol. 6, 2021)
This study was aimed at assessing the microbial population and chemical components of paraquat treated soils. The soil samples were treated with the low (0.3 ml/L), recommended (0.6 ml/L) and high (0.9 ml/L) doses of paraquat respectively. Microbial and chemical assessments were carried out using standard procedures. The results of the study showed that, microbes such as Staphylococcus sp., Micrococcus sp., Pseudomonas sp., Escherichia coli, Bacillus sp., Actinomycetes bovis, Actinomycetes israeli, Streptomycetes sp., Aspergillus fumigatus, Aspergillus niger, Aspergillus flavus, Absidia corymbifera and Rhizopus stolonifer were found present in the paraquat treated soils of different doses with the control soil samples having most of the fungal species isolated. The application of the paraquat to the soils at different weeks after application (WAA) affected the microbes as most were found absent in some of the treated soil samples and this was proved by the result of the control soil samples. The organic matter and carbon contents of the paraquat treated soils were at the 4th WAA had the significantly (P=.05) highest contents with 1.93%, 1.93% and 1.84% and 1.34%, 1.12% and 1.12% respectively whereas the pH of the soils was at 2nd WAA the highest compared to those of the other soils at other WAA as well as the control soils. Different doses of paraquat at different WAA affect soil microbial populations as well as the chemical components of the soil. So, the effects of paraquat on soil microbial population and chemical components depended on the concentrations used and the duration of application. Since the fungi, bacteria and actinomycetes species identified in this study were sensitive to herbicide application, they may serve as a reliable indicator of the biological value of soils. It also determines the type of microbes present in the soil by getting rid of those that cannot withstand its effects, in this way allowing only the resistible species.